2017
DOI: 10.1007/s11634-017-0293-y
|View full text |Cite
|
Sign up to set email alerts
|

Eigenvalues and constraints in mixture modeling: geometric and computational issues

Abstract: This paper presents a review about the usage of eigenvalues restrictions for constrained parameter estimation in mixtures of elliptical distributions according to the likelihood approach. These restrictions serve a twofold purpose: to avoid convergence to degenerate solutions and to reduce the onset of non interesting (spurious) maximizers, related to complex likelihood surfaces. The paper shows how the constraints may play a key role in the theory of Euclidean data clustering. The aim here is to provide a rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 62 publications
(80 reference statements)
0
11
0
Order By: Relevance
“…From the seminal paper of Day (1969) we know that the likelihood for Gaussian mixture is unbounded and the ML approach is thus an ill posed problem, whenever constraints like in (4) are not assumed. Notice further that the constraint in (4) is still needed whenever either the shape or the volume is free to vary across components (García-Escudero et al, 2018): feasible algorithms for enforcing the eigen-ratio constraint under different specification of the covariance matrices as per Figure 2 are reported in Cappozzo et al (2019).…”
Section: Estimation Procedure: Transductive Approachmentioning
confidence: 99%
See 2 more Smart Citations
“…From the seminal paper of Day (1969) we know that the likelihood for Gaussian mixture is unbounded and the ML approach is thus an ill posed problem, whenever constraints like in (4) are not assumed. Notice further that the constraint in (4) is still needed whenever either the shape or the volume is free to vary across components (García-Escudero et al, 2018): feasible algorithms for enforcing the eigen-ratio constraint under different specification of the covariance matrices as per Figure 2 are reported in Cappozzo et al (2019).…”
Section: Estimation Procedure: Transductive Approachmentioning
confidence: 99%
“…Given the semisupervised nature of the problem at hand, we propose to further rely on the information that can be extracted from the robustly initialized estimates { τ , μ, Σ} to set sensible values for the fixed constant c ≥ 1 required in the eigenvalue-ratio restriction. That is, if no prior information for the value c is available, as it is almost always the case in real applications (García-Escudero et al, 2018), the following quantity could be, al least initially, used:…”
Section: Setmentioning
confidence: 99%
See 1 more Smart Citation
“…Starting from a seminal paper by Hathaway (1985), an alternative approach is to constrain the Σ j scatter matrices by specifying some tuning constants that control the strength of the constraints. A fairly comprehensive review of this approach can be found in García-Escudero et al (2018). For instance, a recent proposal following this idea is the "deter-and-shape" one in García-Escudero et al (2020).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, non-interesting local maxima denoted as "spurious" solutions, which consist of a few, almost collinear, observations, are often detected by the Classification EM algorithm (CEM), traditionally applied when maximizing (1), and by the EM algorithm, traditionally applied when maximizing (2). A recent review of approaches for dealing with this lack of boundedness and for reducing the detection of spurious solutions can be found in García-Escudero et al (2018).…”
Section: Introductionmentioning
confidence: 99%